Association between sleep duration and high blood pressure in adolescents: a systematic review and meta-analysis. (17th November 2018) - Jiang, Wen; Hu, Chengyang; Li, Fengli; Hua, Xiaoguo; Zhang, Xiujun
Abstract: Context: Sleep has been assessed as a risk factor for health consequences. Among adults, excessively longer and shorter sleep durations are associated with high blood pressure (BP), but knowledge of the association between sleep duration and high BP among adolescents is limited. Objectives: To estimate the associations between sleep duration and high BP in adolescents. Methods: PubMed, Web of Science, and Cochrane databases were searched for eligible publications up until 20 November 2017. This study reviewed the reference lists from retrieved articles to search for relevant studies. Pooled odds ratios (ORs) were calculated using a random-effects meta-analysis. Sub-group and sensitivity analyses were conducted to identify heterogeneity. Publication bias was evaluated using Egger's test. Results: Seven studies involving 21, 150 participants were included, with ages ranging from 10–18 years. For primary analysis, compared with the reference sleep duration, the pooled OR for high BP was 1.51 (95% confidence interval [CI] = 1.04–2.19) for the short sleep duration overall. For long sleep duration, the pooled OR was 1.04 (95% CI = 0.78–1.38). Further sub-group analysis showed that short sleep duration had a higher risk of incident high BP in males (OR = 1.55, 95% CI = 1.24–1.93) than in females (OR = 1.23, 95% CI = 0.47–3.22). Conclusions: Among adolescents, and particularly male adolescents, short sleep duration may be a risk factor for high BP. More attention should be given to this lifestyle factor.